The Role of Digital Transformation in the Effectiveness of Employee Performance Evaluation: An Applied Study on the Department of Municipalities and Transport in Abu Dhabi - Alameri, Nassib Mubarak Suhail Yatba; Jalil , Muhammad Hilmi; Kawangit, Madya Dr. Razaleigh Muhamat (International Review of Management and Marketing, 2026)
This study aimed to examine the role of digital transformation in enhancing the effectiveness of employee performance evaluation at the Department of Municipalities and Transport in Abu Dhabi through an applied quantitative approach. The study sought to measure the level of digital transformation, assess the effectiveness of employee performance evaluation systems, and analyze the impact of digital transformation on improving accuracy, fairness, and transparency in performance appraisal processes. A descriptive–analytical methodology was adopted, and data were collected using a structured questionnaire distributed to a simple random sample of 326 employees out of a population of 1,754 employees, based on Sekaran and Morgan’s sample size table with a 95% confidence level and a 5% margin of error. The findings revealed that the level of digital transformation at the Department of Municipalities and Transport was high, and the effectiveness of employee performance evaluation was also perceived at a high level in terms of accuracy, fairness, and feedback transparency. Statistical analysis confirmed a strong positive and statistically significant relationship between digital transformation and employee performance evaluation effectiveness, as well as a significant impact of digital transformation on enhancing evaluation outcomes. The study concludes that digital transformation represents a strategic pillar for improving performance management systems in government institutions, contributing to institutional efficiency and sustainable organizational performance.